Imagining alternative futures through the lens of food in the Afghan and Tajik Pamir mountains - Frederik J.W. Van Oudenhoven; L. Jamila Haider (Revue d'ethnoécologie)
Imagining alternative futures in the Pamir Mountains of Afghanistan and Tajikistan is as difficult as it is necessary. Development efforts in the Pamirs are hampered by i) real and imagined agro-ecological limits, ii) terrific geopolitical, institutional and social challenges, and related to both, iii) a strong lack of imagination. This crisis of imagination partly springs from a narrow reading of history, which obscures much of the wealth of the Pamirs and its people, including elements crucial to their ability to develop in a sovereign manner. This paper explores a different development narrative, which emerges when the history of today’s Pamirs, its landscape, agriculture, diversity, and culture are understood, not in terms of empires, humanitarian threats or markets, but through the lens of food. The perspectives presented are drawn from fieldwork conducted over a period of four years in the Pamirs. Using Felix Guattari’s concept of the ‘three ecologies’, we apply these perspectives to an analysis of the three spheres in which development agencies in the region are active : landscape and agriculture, social (economic) relationships, and the human subjectivity of memories, identity and imagination. Viewed through the lens of food, alternatives emerge that may help formulate a more endogenous vision for development.